Complex deformation histories and modeling mechanical behavior of glassy polymers. (22nd February 2023) - Song, Hosup; Medvedev, Grigori A.; Caruthers, James M.; Young Jo, Jun; Kim, Jaewoo
Abstract: Historically the constitutive models for glassy polymers have targeted the stress-strain behavior observed in a single-step experiment – the constant strain rate (CSR) loading. However, a true test of a constitutive model is the ability to predict the complex multistep deformations. When the CSR loading is the last step of a multistep experiment, the magnitude of the stress overshoot depends on the previous steps, thereby providing a sensitive criterion for testing models. A comprehensive set of multistep experiments has been performed on PBMA/MMA copolymer lightly crosslinked with EGDMA for several temperatures below Tg, where the parameters of the intermediate steps have been systematically varied. None of the traditional constitutive models can even qualitatively predict the data. A recently proposed toy model captures the experimentally observed trends. Graphical abstract: Image 1 Highlights: Multi-step deformations are a true test of constitutive models for glassy polymers. Stress overshoot is a sensitive reporter on the thermo-mechanical history. Pre-deformation causes a second stress overshoot to appear. Traditional models fail to predict the second stress overshoot. New model predicts the non-monotonic behavior of the stress overshoot.